NEOTECTONICS OF THE SEA OF OKHOTSK - V. P. Semakin; A. V. Kochergin; T. I. Pitina (Геодинамика и тектонофизика, 2016)
The analysis of the neotectonic structure of the region is usually accompanied by the compilation of neotec‐ tonic maps and schemes. Models of the summit surface serve as the initial material for compiling different‐scale neo‐ tectonic maps and schemes [Ufimtsev, 1984].The summit surface is one of the main properties of the Earth's recent topography (including the land surface and sea bottom) and represents an ideal surface connecting the maximal heights of the present‐day relief of different geo‐ morphologic levels. The universal development of the summit surface allows in to be used for revealing and studying the neotectonic structural elements both on land and seas.When compiling the structural – neotectonic map of the Sea of Okhotsk (Fig. 2), we accepted the polygenetic poly‐ chronous “summit” surface of the sea bottom shown by the isobaths relative to the present‐day sea level as the prima‐ ry (“structural”) one. The map is largely based on data from the bathymetric maps and represents, in fast, a static model of neotectonics. The structural‐neotectonic map served as a basis for compiling the scheme of the principal neotectonic structural elements of the studied region (Fig. 3).For clarifying the formation history of the neotectonic structural elements, we compared their present‐day spatial position relative paleogeographical schemes of the lithophysical complexes (LC), which are united into four regional seismostratigraphic complexes (RSSC) corresponding to the following time intervals: RSSC I to K2–P1‐2; RSSC II to P3–N11; RSSC III to N11‐2; RSSC IV to N13–N2 [Sergeyev, 2006], besides showed general characteristic of the paleo‐ geographical settings that controlled the accumulation of different lithophysical complexes (Fig. 4).